Progress in the Research and Targeted Therapy of ErbB/HER Receptors in Urothelial Bladder Cancer - Chen, Dong; Ye, Yunlin; Guo, Shengjie; Yao, Kao (Frontiers in Molecular Biosciences, 2021)
Bladder cancer is a lethal malignancy and a majority of bladder cancer arise from urothelial cells. Infiltration and metastasis are barriers for the radical cystectomy to achieve favored outcome and are the main cause of death. Systemic therapy, including chemotherapy, targeted therapy, and immunotherapy, is fundamental for these patients. erbB/HER receptors are found to be overexpressed in a subgroup of urothelial carcinoma, targeting erbB/HER receptors in these patients was found to be an efficient way in the era of genetic testing. To evaluate the role of erbB/HER receptors in bladder cancer, we reviewed the literature and ongoing clinical trials as regards to this topic to unveil the context of erbB/HER receptors in bladder cancer, which probably help to solidate the theoretical basis and might instruct further research.